Evaluation of the Properties of 4-Year Old Rubberwood Clones Rrim 2000 Series for Particleboard Manufacture - Al-Edrus, Syeed Saifulazry Osman (2007)
With drastic depleting rubberwood supply, the Lembaga Getah Malaysia (LGM) has identified new clones of rubber trees that are expected to produce not solely latex but also timber. Among these clones, several clones from RRIM 2000 series were found to be fast growing with high yield of latex, high growth vigor, good growth form and are very suitable for timber production, particularly for the biocomposite industries. In this study, particleboards were manufactured from rubber tree clones of RRIM 2002, RRIM 2020 and RRIM 2025 which are also categorized as Latex Timber Clone (LTC). The properties of these particleboards were compared with those made from the currently planted tree clone ; PB 260. All clones from RRIM 2000 series were planted at 1000-1100 trees planting density and harvested for this study at 4 year-old. The resin used was E1-grade urea formaldehyde (UF) and the target density of the particleboard was 700 kgm-3. The basic and adhesion properties of these woods were evaluated and discussed in relation to the board performance i.e. physical and mechanical properties, and dimensional stability. These properties were determined according to Japanese Industrial Standard for Particleboard (JIS A 5908-2003). Among the clones studied, RRIM 2002 showed the best overall wood basic properties and board performance, which are comparable to or better than those of matured clone PB 260. The 25-year old PB 260 gives the highest specific gravity (0.601), lowest moisture content (70%), longer fibre length (1.3 mm) and thickest fibre wall thickness (6.2 μm). Clone RRIM 2002 gives comparable wood basic properties except for specific gravity (0.570), higher wood moisture content (94%) relatively longer fibre length (1.4 mm) and thicker fibre wall (5.5 μm). Except for specific gravity, the other two clones give poorer overall wood properties particularly the RRIM 2025. Both clones, however, produced relatively high specific gravity, 0.589 and 0.582 for RRIM 2020 and RRIM 2025. The adhesion properties of all 4-year old clones show almost similar properties. For the particle analysis, PB 260 gives the highest acceptable particle distribution (63.5%), whilst RRIM 2002, RRIM 2020 and RRIM 2025 had respectively, 56.8%, 57.9%, 58.3%. The particleboards of PB 260, RRIM 2002, RRIM 2020 recorded similar modulus of elasticity (MOE) of 2156 Nmm-2, 2145 Nmm-2, and 2122 Nmm-2, respectively, which were significantly higher (p< 0.05) than that of RRIM 2025 board (1931 Nmm-2). The board’s strength (MOR) of clones RRIM 2002, RRIM 2020, RRIM 2025 and PB 260 were 20.4 Nmm-2, 19.9 Nmm-2, 18.0 Nmm-2 and 21.0 Nmm-2, respectively. The internal bond (IB) of all of the boards ranged from 1.24 Nmm-2 to 1.49 Nmm-2, and were not significantly different. Among the four rubber tree clones, PB 260 board was the most stable as indicated by the low values in thickness swelling (RRIM 2002, 22.4 %; RRIM 2020, 21.2 %; RRIM 2025, 19.7 % and PB260, 18.1 %). No significant difference in water absorption of particleboard was found for all clones studied. The overall results indicate that 4-year old rubberwood clones can be used as raw material for particleboard manufacture where clone RRIM 2002 as the most suitable clone as it produced comparable particleboard properties with matured clone particleboard.